Tu es Petrus – super hanc petram aedificavi cursum meum - Curry, Robert (Res Facta Nova, 2022)
The book under review is the first monograph-length study devoted to the works of the enigmatic composer, Petrus Wilhelmi de Grudencz. The paucity of information about the composer’s life and about the historical circumstances surrounding his works poses a daunting methodological challenge. The aplomb with which the author, Paweł Gancarczyk, has met this challenge attests to the depth of his knowledge of Petrus Wilhelmi’s works; furthermore, it reflects his thorough conversance with a multiplicity of relevant sources, compositions (not a few in fragmentary state), institutions and personalities. The review notes the manner in which Gancarczyk has thoughtfully interwoven contextual inference, logical extrapolation and informed conjecture to sustain a fluent and engaging narrative. Due attention in the review is given to the author’s contention that the works of Petrus Wilhelmi can be regarded as archetypical of fifteenth-century Central European music. The review acknowledges Gancarczyk’s book as an invaluable compendium of up-to-date data and information about Petrus Wilhelmi and his oeuvre.